Factors associated with hygiene practices among primary school children in southern Ethiopia - Bamlaku Golla, Eyasu; Leta, Dawit Denano; Abate, Alegntaw; Geremew, Habtamu; Abdisa Kuse, Samuel (Frontiers in Public Health, 2024)
Background Eight years into the Sustainable Development Goal period, Ethiopia is not on track to achieve good hygiene practices among school children. Ensuring good hygiene practices among primary school children to prevent the spread of communicable diseases remains a challenge in most primary schools in Ethiopia. Therefore, the aim of this study was to identify factors associated with hygiene practices among primary school children in southern Ethiopia. Methods A school-based cross-sectional study was conducted from June 3 to July 28, 2022, in five primary schools. The simple random sampling technique was used to select the school. Subsequently, 640 students were selected from the proportionally allocated sample size. Pretested semi-structured interviewer-administered questionnaires and observational checklists were utilized to collect data. The data was then entered into EpiData version 4.6 and analyzed using SPSS version 25. Variables with a p ≤ 0.25 at bivariate analysis were used to develop a multivariable logistic model to identify factors associated with hygiene practices. P < 0.05 with a 95% confidence interval was considered statistically significant. Results The magnitude of overall good hygiene practices was 29.2% (95% CI: 25.81–32.59). Urban residence (AOR = 3.4, 95% CI 2.1–5.55), knowledge of handwashing (AOR = 4.5, 95% CI 2.8–7.36), being a member of a hygiene and sanitation club (AOR = 3.7, 95% CI 2.4–6.86), and experience of visiting a model school (AOR = 3.1, 95% CI 2.1–5.55) were found to be significantly associated with hygiene practices. Conclusion The overall level of good hygiene practices in Kedida district was low. Therefore, it is essential to enhance health education on handwashing, establish sanitation and hygiene clubs, and conduct visits to district model elementary schools.